The Impact of Creativity and Innovation on Increasing Micro Enterprise Income PKL Gading Fajar Sidoarjo - Arif Syaifudin (IJEBD (International Journal of Entrepreneurship and Business Development), 2017)
The purpose of this research first to identify and analyze variables influence creativity and innovation simultaneously towards entrepreneurship. Second, to identify and analyze variables influence creativity partially towards entrepreneurship. Third, to identify and analyze the partial effect of the innovation variables on entrepreneurship. Fourth, to identify and analyze the dominant influence between creativity and innovation of entrepreneurship.. Design/methodology/approach : This type of research is exploratory. Types of data used are data collected by primary and save a list of questions. Findings : The results are as follows: first, variables influence creativity and innovation simultaneously towards entrepreneurship. Second, creativity variables partially influence on entrepreneurship. Third, innovation variables partially influence on entrepreneurship. Fourth, innovation variables have the most impact on entrepreneurship. Research limitations/implications : Location of the research done on small welding shop in the district of Sidoarjo. Practical implications : The essence of entrepreneurship is the ability to create something new and different through creative thinking and innovative action to create opportunities. Originality/value : The role of SMEs can be said to be very important in the national economy. The role is mainly in the aspects such as increased employment opportunities, equity, income, rural economic development, and increase non-oil exports. Entrepreneurship is the ability to be creative and innovative basic, tips, and resources to look for opportunities to success.